Isolated pyosalpinx in a pre-teen with bicornuate uterus - Muhammad Afzal; Mukul R. Kothari; Ayman T. Alghasham; Muhanad M. Attal (Elsevier, 2021)
Pyosalpinx is a condition usually seen in a sexually active female. In literature, only a few cases have been reported in a virginal girl presenting with pyosalpinx. Herein we report a case of an 11-year-old virginal girl with pyosalpinx treated by laparoscopic drainage and antibiotics.